A cloud-based approach to dynamically manage service contracts for local public transportation. (9th August 2019) - Longo, Antonella; Zappatore, Marco; Bochicchio, Mario A.
Public contracts regulate how public services are managed by the stakeholders. However, the current technological trend is creating a significant bias between the pace at which service data are produced and that at which contracts change. This increased availability of service data can be exploited in public procurement processes by fostering novel approaches to manage contracts, making them more dynamic and improving the Quality of Service (QoS) delivered to customers. In this paper, a cloud-based approach for assessing the QoS in Local Transportation Services (LTSs) in Apulia Region (Southern Italy) is proposed. Service Level Agreements (SLAs) between providers and the Regional Authority, as well as the minimal guaranteed QoS levels between providers and passengers, are modelled as contracts enacted via a cloud-based system, which gathers data from sensors and passengers. In this way, changes in contract conditions for improving the perceived and delivered QoS can be fastened and facilitated based on data. In order to validate the pilot case, a set of quality indicators and service levels grounded in European and Italian regulatory frameworks has been considered.